Legal Dimensions of International Framework Agreements in the Field of Corporate Social Responsibility - Sobczak, André (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2007)
The aim of this article is to offer an in-depth analysis of the different legal aspects of international framework agreements (IFAs) negotiated between multinational companies and global union federations. Using examples from different agreements, the article shows the potential added value IFAs have in contributing to an effective social regulation within international groups and global supply chains that are today regulated insufficiently by national, European and international labour law standards. It also analyses the impact of the international negotiation process of the IFAs and the powers of the signatory parties on the legally binding character of these texts. To conclude, the article discusses the potential added value of an optional legal framework for IFAs.